Effect of Tailings Fine Content on the Properties of Cemented Paste Backfill from the Perspective Packing Density - Haijun Wang; Xiaogang Sun; Jianwen Wang; Yun Duan; Changsuo Zhang; Jingping Qiu; Zhenbang Guo (Advances in Civil Engineering)
In order to quantitatively study the influence of tailings fine content on the properties of cemented paste backfill (CPB) and further understand the mechanism of tailings fine content acting, the concept of packing density was introduced in this study. The packing density of each tailings sample was measured by the wet packing method after the samples with various fine contents were prepared. Moreover, CPBs with different tailings fine contents were tested by the mini slump test, rheological test, uniaxial compressive strength (UCS) test, and mercury intrusion porosimetry test. The results demonstrated that the flow spread and UCS both increase first and then decrease with the increase of tailings fine content, while the yield stress shows an opposite trend. The fine content of tailings affects the flowability of fresh CPB mainly through the packing density. When the fine content is high, the influence of the specific surface area of tailings cannot be ignored. The packing density is an important factor affecting the strength of CPB, and there is an obvious linear relationship between the packing density and UCS. The pore structure of CPB samples with different tailing fine contents is significantly different, and the macroscopic packing density changes the strength of CPB by affecting the microscopic pores.